2017
DOI: 10.1002/icd.2033
|View full text |Cite
|
Sign up to set email alerts
|

Infants' emotional expression: Differences in the expression of pleasure and discomfort between infants from Chile and the United States

Abstract: Nonverbal cues have been fundamental to the survival of our species, and they remain a critical aspect of communication. Starting at the moment of birth, children's facial expressions and body gestures reflecting pleasure and discomfort elicit different responses from caregivers, which can shape the trajectory of child development. Although early expressions of emotion are universal, socialization of the intensity of expressions begins in infancy and may be influenced by the place the child is born, family cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 52 publications
1
1
0
1
Order By: Relevance
“…children are better with request tasks than with imitation tasks) [6]; and (4) ethnic and cultural factors (e.g. cross-cultural studies indicate that the intensity of spontaneous expression is not universal and may vary across cultures) [10,11]. Similarly, in a previous study [6], we found that children from the south of France (Nice) were more expressive than children from the north (Paris).…”
Section: Introductionsupporting
confidence: 69%
“…children are better with request tasks than with imitation tasks) [6]; and (4) ethnic and cultural factors (e.g. cross-cultural studies indicate that the intensity of spontaneous expression is not universal and may vary across cultures) [10,11]. Similarly, in a previous study [6], we found that children from the south of France (Nice) were more expressive than children from the north (Paris).…”
Section: Introductionsupporting
confidence: 69%
“…These findings showed that ethnicity can influence the production of emotion but also that culturally based family environment modulates the effect of ethnicity. Moreover, this effect seems to appear in the 1st year of life ( Camras et al, 2007 ; Muzard et al, 2017 ).…”
Section: Introductionmentioning
confidence: 98%
“…Desde que un niño nace, los gestos y las expresiones faciales demuestran el placer y la incomodidad según los estímulos del ambiente al que se ven sometidos y de acuerdo con las necesidades interiores que experimentan (hambre o sueño, entre otras). Son justamente las expresiones faciales y su intensidad lo que permite inferir dichas necesidades en los lactantes por parte de los cuidadores, lo que va delimitando la trayectoria vital del infante (Muzard et al, 2017). En consecuencia, las expresiones faciales pueden ser entendidas como adaptativas, y juegan un papel muy importante pues expresan las necesidades del bebé, asimismo logran provocar respuestas en sus cuidadores (Mesman et al, 2012), y permiten que los mismos infantes en las diferentes circunstancias moldeen la expresión emocional hacia formas socialmente apropiadas de funcionamiento en una cultura en específico (Trommsdorff y Cole, 2011).…”
Section: Aspectos Destacados Del Trabajounclassified